Effects of various nutrients on growth of chlorella - Wong, Mei-ling; Hanaki, K.; Chongrak Polprasert; Sarnorn Muttamara; Australian Government (Bangkok : Asian Institute of Technology, 1987)
This study was carried out to investigate the types and quantities of nutrients, which caused excessive growth of Chlorella in water bodies. Tap water and distilled water were used as the water medium for the experiments. Batch experiments were carried out by introducing different types and amount of nutrients into 250ml conical flasks that contained 200ml of either tap water or distilled water. The same amount of inoculum algae was added each time and the sample was cultivated under the same condition of temperature and constant light intensity (1076 Lux). Growth was measured in terms of the amount of chlorophyll-a. Different forms of nitrogen (ammonia, nitrate and nitrite) were found to have different effects on algal growth. The results show that higher concentration of ammonia caused the higher algal growth in tap water. Nitrate and nitrite gave less effect on algal growth . Higher algal growth was achieved in tap water than distilled water even though same amounts and same types of inorganic nutrients were added. Phosphorus was found to have no effect on algal growth in tap water when 0.01 to 2 mg/L of P was added. River water by itself was unable to sustain high algal growth. But addition of 5 mg/L of ammoniated to the increase of algal growth . Oxidation pond effluent with or without the addition of 5 mg/L of ammonia gave almost the same growth. It is possible that other elements may be the limiting factor for growth. Sewage treatment plant effluent, on the other hand, contained high amount of ammonia which resulted in very high algal growth.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Eutrophication; Algae